Răspuns :
[tex] \int\limits^6_5 { \frac{1}{(x-4)^2} } \, dx=- \frac{1}{x-4} [/tex][tex] I\limits^6_5[/tex]=-[1/(6-4)-1/(5-4)]=1/2
derivata lui [tex] \frac{1}{x-4} [/tex] este [tex]- \frac{1}{(x-4)^2} [/tex], deci invers integrala este [tex] \frac{1}{x-4} [/tex]
derivata lui [tex] \frac{1}{x-4} [/tex] este [tex]- \frac{1}{(x-4)^2} [/tex], deci invers integrala este [tex] \frac{1}{x-4} [/tex]
[tex]\it I = \int\limits^6_5{\dfrac{1}{(x-4)^2}}\ dx
[/tex]
Notam x - 4 = t ⇒ dx = dt și vom avea:
[tex]\it \int{\dfrac{1}{(x-4)^2}}\ dx = \int{\dfrac{1}{t^2}}\ dt = \int{t^{-2}} \ dt = \dfrac{t^{-2+1}}{-2+1} +C = \\ \\ =\dfrac{t^{-1}}{-1} +C = -\dfrac{1}{x-4} +C[/tex]
[tex]\it I = \int\limits^6_5{\dfrac{1}{(x-4)^2}}\ dx = -\dfrac{1}{x-4} |^6_5 =-\dfrac{1}{6-4} + \dfrac{1}{5-4} =-\dfrac{1}{2} +1 =\dfrac{1}{2}[/tex]
Notam x - 4 = t ⇒ dx = dt și vom avea:
[tex]\it \int{\dfrac{1}{(x-4)^2}}\ dx = \int{\dfrac{1}{t^2}}\ dt = \int{t^{-2}} \ dt = \dfrac{t^{-2+1}}{-2+1} +C = \\ \\ =\dfrac{t^{-1}}{-1} +C = -\dfrac{1}{x-4} +C[/tex]
[tex]\it I = \int\limits^6_5{\dfrac{1}{(x-4)^2}}\ dx = -\dfrac{1}{x-4} |^6_5 =-\dfrac{1}{6-4} + \dfrac{1}{5-4} =-\dfrac{1}{2} +1 =\dfrac{1}{2}[/tex]